A comparative study of p53 expression in hyperplastic , dysplastic epithelium and oral squamous cell carcinoma - Sucheta Bansal; Keya Sircar; Sanjeev Kumar Joshi; Sanjeet Singh; Varun Rastogi (Universidade Estadual de Campinas, 2015)
Aim: To study oral hyperplastic epithelium, dysplastic epithelium and squamous cell carcinoma to determine (1) the prevalence of p53 protein immunoreactivity, (2) number of p53 positive cells, and (3) the area of localization of p53 protein immunoreactivity. Methods: Two contiguous sections from 30 tissue specimens (10 each from oral hyperplastic epithelium, dysplastic epithelium and squamous cell carcinoma) were subjected to hematoxylin and eosin (H/E) staining for histopathological diagnosis and immunohistochemical (IHC) staining for demonstration of p53. p53 positivity was looked for in each IHC stained slide and the number of positive cells amongst 1,000 epithelial cells were recorded. The localization of these p53 positive cells within the strata (i.e. basal/suprabasal, spinous and superficial layers) of epithelium between 3 groups, and also within each group according to histological grades was recorded. Results: Higher p53 positive cell counts were demonstrated in oral squamous cell carcinoma compared to hyperplastic and dysplastic tissues. The expression of p53 in epithelial hyperkeratosis was mainly localized to basal epithelial cells whereas in epithelial dysplasia, it was predominantly localized to spinous epithelial cells. Conclusions: Qualitatively p53 is not a specific marker for malignancy of oral epithelium. However the quantitative analysis of p53 positive cells and their localization in oral epithelium is of importance as a marker for oral squamous cell carcinoma.